Humanization and Action (Revista Iberoamericana de Bioética, 2018)
This paper reviews the meaning of the word humanize and the basis of humanization understood as vulnerability and dignity. The key areas for humanization are summarized, such as the political-economic sphere, justice, structures, culture and the inter-personal relationship. The causes of humanization, such as injustice, power, ignorance and technological development, de-personalization, bureaucratization, corruption, pain and suffering and lack of training are looked into in depth. Finally, humanizing actions that include the reviewed areas are proposed.
Keywords: humanization; bioethics; areas of humanization; causes of humanization